PENGANALISIS KESEGARAN DAGING SAPI DAN DAGING BABI MENTAH BERDASARKAN KLASIFIKASI WARNA DAN KELEMBABAN - Nadya Ayu Nafiasari; Ariesta Martiningtyas Handayani (Jurnal Teknosains, 2018)
There are many frauds involving the trade of beef. Traders do the fraud by replacing the beef it sells with pork. Also, the lack of consumer knowledge of the difference between beef and pork make these traders unscrupulous. Because we research by designing and creating systems that can identify and analyze the freshness of beef and pork. This system uses a color sensor as a color identifier in meat and humidity sensors to measure the level of freshness of meat. Also used is also a microcontroller as an acquirer and data processor. This system is designed to distinguish between beef and pork. This study involved data collection on beef and pork as much as 420 data. These data have shown that this system has an accuracy of 79%, 80%, 80%, 83%, 77% and 81% in identifying fresh beef, fresh pork, less fresh beef, less fresh pork, the cow is not fresh, and the pork is not fresh in sequence. This system is portable because it can be taken anywhere with a battery that supplies the power of this tool. With this system, consumers can distinguish between beef and pork and can know the level of freshness in each meat.